Luminescent lanthanoid complexes of a tetrazole-functionalised calix[4]arene - D’Alessio, Daniel; Muzzioli, S.; Skelton, B.; Stagni, S.; Massi, Massimiliano; Ogden, Mark (Royal Society of Chemistry, 2012)
p-t-Butylcalix[4]arene functionalised at the lower rim with two tetrazole moieties is found to be a useful receptor for lanthanoid cations. The luminescence of the resulting complexes can be controlled by addition of base, with emission achieved in the visible and infrared regions.